Antecedents of Online Impulse Buying: An Analysis of Gender and Centennials’ and Millennials’ Perspectives - Cavazos-Arroyo, Judith; Máynez Guaderrama, Aurora (2022)
Impulse buying continues to be a relevant topic for retail management, yet few studies have examined the role of online impulse buying. This study analyzes the effect of impulse buying tendency on online impulse buying behavior through the mediation of normative evaluation and the urge to buy impulsively on the Internet. As a secondary objective, we aim to identify whether gender and generation influence the model. The research was conducted in Mexico with millennials and centennials who had previously bought products on the Internet. We used quantitative, explanatory, non-experimental, cross-sectional research. We applied an electronic survey, and, for the statistical technique, we used PLS. According to the results, impulse buying tendency both directly and indirectly influences online impulse buying behavior through the mediating roles of normative evaluation and the urge to buy impulsively on the Internet. Moreover, we found that gender does not have an effect on the model. Regarding generation, two significant differences were found between centennials and millennials